Fomento de habilidades científicas en estudiantes de la carrera de EGB I y II Ciclos: una experiencia inter-cátedras (Repertorio Científico, 2024)
This study, conducted under the thematic axis of pedagogical mediation in virtual environments, aims to disseminate the experiences carried out during the second quarter of 2022 between the Didactics of Natural Sciences Department of the School of Education Sciences and the Physics for Engineering Department of the School of Exact and Natural Sciences at the Universidad Estatal a Distancia. The purpose is to foster the development of scientific skills in the training of future primary education teachers. This has been made possible through the implementation of the Extended Laboratory model, which relies on the use of technological resources such as Remote Laboratories and the design of Simple Experimental Activities. In conjunction with an appropriate educational process route that includes didactic guides, content contextualization, and formative assessment, significant modifications have been made to the teaching and learning methodology of natural science II subject for primary education. A qualitative and descriptive methodology with a phenomenological design was followed to systematize the socialization of the inter-departmental experience and to interpret the data from the questionnaire administered to 113 students to determine the scientific skills developed in the primary science subjects. The research findings revealed challenges for students in the first and second cycles of the program in terms of activity development and evaluation model, thus concluding that the changes generated in the subjects directly impact the type of knowledge acquired by students in a distance learning model with virtual components.